Multilateralism: Variants, potential, constraints and conditions for success - Hanns W. Maull (Stiftung Wissenschaft und Politik (SWP), 2020)
In view of the current challenges facing world politics and its specific structural conditions (national sovereignty, power diffusion), multilateralism appears to be an almost indispensable form of international diplomacy. Nevertheless, it seems controversial: multilateralism is currently under fire, particularly from the White House and the State Department, whilst both China's President Xi Jinping and his Russian counterpart Vladimir Putin pose as advocates and defenders of multilateralism. On closer inspection, however, the controversy is not about multilateralism as a diplomatic procedure, but essentially about the question of which principles, values and organizations should determine the international order and thus shape international politics. At the same time, the inherent difficulties and limitations of multilateralism are often underestimated, and its potential overestimated. In order to make multilateralism as effective as possible, a realistic assessment of its preconditions and a wise understanding of the peculiarities of multilateral politics are therefore essential.
Keywords: 320